An Applied Linguistics Study of Teaching Tourism English to Management Students at Dhyana Pura University - I Nengah Laba; Komang Astiari; I Wayan Budiarta (International Journal of Linguistics and Discourse Analytics, 2026)
This study investigates the application of applied linguistics principles in the teaching of Tourism English for travel agents within an English for Specific Purposes (ESP) framework at Dhyana Pura University. The research aims to examine the extent to which instructional practices align with the communicative needs of travel agents and how such practices support the development of students’ communicative competence. A qualitative descriptive design was employed with data collected through classroom observation, documentation, and analysis of students’ written tasks. The data were analyzed using an integrated framework combining ESP components and communicative competence, including linguistic, sociolinguistic, pragmatic, and discourse aspects. The findings reveal that while Tourism English instruction incorporates relevant vocabulary and basic communicative tasks, its alignment with real-world professional contexts remains partial. Students demonstrate moderate linguistic competence but face challenges in grammatical accuracy, sociolinguistic appropriateness, pragmatic effectiveness, and discourse organization. These limitations indicate that instruction has not yet fully integrated communicative competence into authentic task-based learning. This study highlights the need for a more holistic pedagogical approach that integrates ESP principles with applied linguistics insights. It contributes to the development of Tourism English instruction by emphasizing the importance of authentic tasks, pragmatic awareness, and discourse-level competence in preparing students for professional roles as travel agents.